2x+12=x-5/3

Simple and best practice solution for 2x+12=x-5/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+12=x-5/3 equation:



2x+12=x-5/3
We move all terms to the left:
2x+12-(x-5/3)=0
We add all the numbers together, and all the variables
2x-(+x-5/3)+12=0
We get rid of parentheses
2x-x+12+5/3=0
We multiply all the terms by the denominator
2x*3-x*3+5+12*3=0
We add all the numbers together, and all the variables
2x*3-x*3+41=0
Wy multiply elements
6x-3x+41=0
We add all the numbers together, and all the variables
3x+41=0
We move all terms containing x to the left, all other terms to the right
3x=-41
x=-41/3
x=-13+2/3

See similar equations:

| {X+2y=3 | | 18^(2x-1)=100 | | 23x-12x=56 | | 4/3=1/9x-2/3 | | 56=6y+y | | (4)/(3)=(1)/(9)x-(2)/(3) | | 2x^2+25x-7.7=0 | | 15=3y=6 | | 5^y=3125 | | x^2-66x-5=0 | | 2x+4-x+8=5x-2 | | (1/2)x+7=20 | | (7x-1)-(2x-)=x+ | | 5(4y+3)+13=3(3y+2)-10 | | 7(2y-1)=22 | | 10x+13x-13=-13x+8 | | 14y=2 | | -5(x+4)+2=-7(x-8) | | 8x+16+5x=180 | | -10x-2=7x-18 | | 6(4x+4)=6x+11 | | 4x-7×=13 | | (8x-3)+(6x+7)=180 | | 400+0.05s=200+0.09s | | $400+0.05s=$200+0.09s | | 90+(3x+2)+x=180 | | y=2.667/11.33 | | 7.1x-8=2.1x+17= | | 12y=2.667+.667y | | -216=1+7(1+8m) | | 3/2x+6=21-7/2x= | | 3/2x+6=21-7/2= |

Equations solver categories